APRENDIZAGEM AUTÊNTICA COM O USO DA ROBÓTICA EDUCACIONAL NO ENSINO DE SISTEMAS EMBARCADOS (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This work aims to analyze the students' perceptions regarding the use of authentic learning with the support of the use of educational robotics in the learning of embedded systems. Educational or Pedagogical Robotics is a teaching methodology that aims to promote in the student the investigation and materialization of the concepts learned, going much beyond the construction of projects and robot programming. It provides a practical and authentic learning that develops in the student the capacity to think and to find solutions to the proposed challenges. In this approach, educational tools such as the Arduino electronic prototyping platform, the Scratch, Tinkercad and Padlet, software was used to learn robotic notions in order to improve students' logical thinking. After twenty-one surveys (n = 21), using the ANOVA analysis, we obtained that the average satisfaction with reference to the approach was positive, motivating students' interest in the subject.
Keywords: Authentic Learning; Educational Robotics; Industrial Automation; Embedded Systems